Nanopartículas metálicas depositadas em suportes inorgânicos : uma combinação eficiente para a preparação de novos catalisadores para a redução de poluentes orgânicos ambientais - Azevedo, Camila Kauany da Silva (2017)
The compound 4-nitrophenol (4-NP) is widely used as a raw material in the production of pesticides, herbicides and synthetic dyes and it is a very common organic pollutants in industrial effluents. This compound is highly toxic even at trace levels and it has high solubility and stability in aqueous media as well as other phenolic derivatives, however it is important to convert it to less toxic products. Several methods have been described in the literature for the removal of 4-NP, including catalytic hydrogenation employing metal nanoparticle as catalysts. By this method, the reaction is conducted under mild conditions at room temperature and it use water as the solvent, in addition, there is the possibility of reuse of the catalyst making the process eco-friendly. Metal nanoparticles exhibit excellent catalytic activity, however, they require stabilizing agents (for example: surfactants or solid supports) to maintain the stability and prevent their aggregation. Thus, in this study hybrid catalysts based on metal nanoparticles and inorganic supports were used in the reduction reaction of 4-NP to 4-aminophenol (4-AP). Hybrids based on gold metal nanoparticles (AuNPs) and iron (III) oxihydroxide (AuNPs/FeOOH); and silver nanoparticles (AgNPs) and layered nitrate zinc (AgNPs/ZHL) were prepared. The synthesis of the nanoparticles was performed by means of in situ reduction reaction of the metal precursors. For the AgNPs/ZHL hybrid, the Ag+ ions were reduced without the use of external reducing agent only employing ethyl alcohol both as solvent and reducing agent in the presence of ZHL support and visible light. Several characterization techniques were used for study the hybrids and the results indicated the presence of metallic nanoparticles with spherical morphology adsorbed on the surface of the inorganic hosts. So, the catalytic activity of the hybrids materials were investigated by the reduction reaction of 4- NP to 4-AP in the presence of sodium borohydride (NaBH4) at room temperature. The hybrids presented excellent catalytic activity with 4-NP total reduction reaction time of 4 min and 5 min for the AgNPs/ZHL and AuNPs/FeOOH catalysts, respectively, both catalysts with higher amounts of metallic nanoparticles. The results also indicated that the catalysts (AuNPs/FeOOH and the AgNP/ZHL) used in this work are promising materials for the remediation of environmental organic pollutants. Moreover, the AgNPs/ZHL hybrids have also the advantage of reuse in various catalytic cycles.